ISU KETUANAN MELAYU DI MALAYSIA: THE ISSUE OF POLITICAL SUPREMACY OF THE MALAY IN MALAYSIA - ,Universitas Indonesia, Indonesia, Amri Marzali (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract This article discusses an important political concept in Malaysia, that is the political supremacy of the Malays. The Malays supremacy was resulted from a social contract between the native Malays, on one part, and the Indian and Chinese immigrants, on the other part, during the negotiation concerning the independent of Persekutuan Tanah Melayu before 1957. It was said in the contract the native Malays slackened the prerequisites for the citizenship of the Persekutuan Tanah Melayu for the Chinese and Indian immigrants, while the Chinese and the Indian immigrants admitted a dominant position of the Malays in political administration. However, after the Persekutuan Tanah Melayu changed into Malaysia in 1963, the Chinese and the Indians begin to be disloyal to the social contract. They wanted equal right among all Malaysian citizens. By using archaeological dan ethnohistorical approaches, I will trace the origins of the concept of native supremacy in the Malay Nusantara sosiocultural context. Secondly, I will discuss the challenges facing the concept after Malay Land occupied by the British colonialist, particularly after the 1960es. The concept of “native sovereignity” is called beschikkingsrecht in Dutch language. It was invented by a Dutch expert of customary law, van Vollenhoven, in 1909 (ter Haar 1962). The concept of “native sovereignity” was originally aimed to remind the neighbour villagers or the foreigners when they passed on, or open a rice field, in a new area. They had to ask permission to the master of the land. Therefore, for the sake of harmonious social life, all ethnic groups in todays Malaysia, especially the new immigrants from different cultural background, it is suggested to learn and comprehend basic concepts in traditional native Malays customary law. Keywords: native Malays, ethnicity, native sovereignity, beschikkingsrecht, Will of the Malay Kings. Abstrak Makalah ini membahas satu konsep politik dalam negara Malaysia, iaitu hak ketuanan Melayu. Ketuanan Melayu adalah hak politik orang Melayu hasil kesepakatan sosial antara kaum peribumi Melayu dengan imigran pendatang dari China dan India menjelang kemerdekaan negara Persekutuan Tanah Melayu. Pada satu pihak, kaum peribumi Melayu memberi kelonggaran syarat kerakyatan (citizenship) bagi pendatang China dan India, sebaliknya pihak kaum pendatang menerima hakikat kedudukan istimewa kaum peribumi Melayu dalam bidang politik. Namun demikian, setelah Persekutuan Tanah Melayu berubah menjadi Malaysia pada tahun 1963, kaum Cina dan India mengkhianati kontrak sosial. Mereka menuntut persamaan hak bagi seluruh warganegara Malaysia dan semua bidang kehidupan. Dengan menggunakan pendekatan arkeologis dan etnohistoris, penulis ingin membincangkan asal-usul daripada konsep hak ketuanan Melayu dalam konteks sosiokultural Melayu Nusantara. Setelah itu akan dibahas cabaran-cabaran yang dihadapi konsep itu setelah Tanah Melayu jatuh ke tangan penjajah Eropah, terutama selepas 1960-an. Konsep “hak ketuanan” atau beschikkingsrecht dalam bahasa Belanda, ditemukan oleh ahli hukum adat, van Vollenhoven, pada tahun 1909 (ter Haar 1962). Konsep ketuanan Melayu memang berpunca dari kata “tuan,” namun kata tuan ini tidak bererti lawan daripada “hamba,” tetapi merujuk kepada pengertian sovereignty atau daulat dalam bahasa Melayu. Konsep hak ketuanan terutama dimaksudkan untuk mengingatkan penduduk desa jiran atau orang dagang supaya berhati-hati ketika melintas, memasuki, atau membuka ladang di sebuah kawasan. Mereka harus mendapat kebenaran daripada penguasa komuniti berkenaan. Demikianlah, demi kehidupan sosial yang harmoni, semua pihak di Malaysia masa kini, terutama kaum pendatang Cina dan India, sebaiknya mempelajari dan memahami konsep-konsep kultural dasar dalam kehidupan politik, ekonomi, dan sosial peribumi Malaysia. Kata Kunci: peribumi Melayu, etnik, hak ketuanan, beschikkingsrecht, Wasiat Raja-raja Melayu.